Musculoskeletal complaints and stress level related to the life habits of university students during the pandemic (Research, Society and Development, 2022)
Objective: To investigate musculoskeletal complaints and the level of stress in university students related to life habits during the pandemic. METHODOLOGY: This project is a cross-sectional quantitative study, through field research. Academics from the Physiotherapy, Medicine, Biomedicine, Psychology, Biology, Accounting Sciences, Economic Sciences, Fisheries Engineering, Administration, Mathematics, Pedagogy and Tourism courses at the Universidade Federal do Delta do Parnaíba were invited to participate, who were between 18 and 45 years old and who joined remote teaching, those who did not answer all the questions and/or who withdrew from the research were excluded. The research took place through the application of virtual questionnaires, sent via SIGAA to all students. Results: A total of 116 university students participated in the research, 90.5% of them reported having had involvement in at least one region, where the most affected places were the upper and lower back (61.2%), wrists/hands (52.6 %) and neck (49.1%), with the highest prevalence of pain in females. It was also found that women have a higher level of stress (25.1 (±6.26)). And, when stress was compared with sleep, it was noticed that those who had poor or very poor sleep had a higher score (26.9 (±6.3)). Conclusion: A high number of musculoskeletal complaints was identified, mainly among females. In addition, stress was also considered another very common problem among students, especially among women and those who have poor sleep.